Implementación de un sistema de administración financiera para la asociación del personal docente, administrativo y de servicio del colegio técnico "San camilo" - Rosero Loor, Justina Liseth (2012)
The development of this work is to build a Financial Management Software for the Association of Teachers, Administrative Service and Technical College "San Camilo" in order to bring a swift and safe accounts management using technologies software development. To carry out this research project is the design methodology used rapid application development (RAD) for the development stage and the quasi-experimental method with a single group design with pretest and posttest for the investigation phase. For software development we used the following tools:  Microsoft Visual Studio 2008  SQL Server 2008 The features offered by these technologies are very large, are efficient and allow developers to quickly create applications. Once implemented the software is able to determine that the management of financial loans takes less time than it normally did, plus the error rate decreased significantly in accounting records